Evaluation of structural, magnetic and concentration dependent texture variations of electrodeposited cobalt nanowires. (December 2022) - Irshad, Muhammad Imran; Ahmad, Pervaiz; Khalid, Awais; Alam, Md Mottahir; Sobahi, Nebras; Din, Israf Ud; Nazir, Ruqia; Alharthi, Abdulrahman I.; Rehman, Fida; Yar, Asfand; Haleem, Yasir A.; Wattoo, Abdul Ghafar; et al.
Abstract: Anodized aluminum oxide (AAO) templates have been used to synthesize Cobalt (Co) nanowires (NWs) by employing the electrodeposition technique as a function of cobalt ions concentration. Cobalt NWs show a strong dependence on cobalt ions concentration, applied during synthesis, in with reference to their structural and magnetic properties. The Co hexagonal (HCP) phase dominates X-ray diffraction, with the (002) plane oriented perpendicular to the NW long axis with lower applied deposition potential and parallel to the NW long axis at higher Co ions concentration. The reorientation of (002) HCP plane and evolution of face-cantered cubic phase (FCC) at higher concentrations of Cobalt ions results in easy axis of magnetization is switched to the long axis of NW from parallel. Co-NWs crystalline structure and magnetic characteristics might be adjusted based on Co ion concentration during synthesis.